A new bipyridyl cobalt complex for reductive dechlorination of pesticides. (20th July 2016) - He, W.Y.; Fontmorin, J.-M.; Hapiot, P.; Soutrel, I.; Floner, D.; Fourcade, F.; Amrane, A.; Geneste, F.
Abstract: Reductive dechlorinations are especially promising reactions for improving the biodegradability and hence decreasing the environmental impact of chlorinated organic pollutants. In this context, the catalytic activity of a bipyridyl cobalt complex containing two bipyridine ligands was examined for achieving clean electrochemical dehalogenation in aqueous media. The prepared [Co(bpy(CH2 OH)2 )2 ] 2+ complex was found to exhibit high catalytic activity toward the dechlorination of chloroacetanilide herbicides. Based on preparative electrolyses, 2-electron reduction of the substrate was obtained with a dechlorination yield of 85%, underlining the selectivity and efficiency of the dehalogenation process. Cyclic voltammetry analyses highlighted the catalytic activity of the complex toward chloroacetanilide herbicides, as alachlor, metolachlor and metazachlor. An high apparent chemical rate constant k1 of 5000 mol −1 L s −1 is calculated for the first step of the cathodic reduction of alachlor, based on simulated cyclic voltammetry experiments.